Student Perceptions of Online Learning Application Effectiveness - Fauzi, Chairul; Ernawati; Ruslan Abdul Gani (STMIK Indonesia Banda Aceh, 2025)
This study aims to explore students’ perceptions of the effectiveness of online learning applications in supporting academic learning. The research was conducted using a quantitative descriptive method involving [number] students from [institution or study program], who have used various online learning platforms such as Google Classroom, Zoom, and Moodle during their learning activities. Data were collected through a structured questionnaire focusing on user experience, ease of access, interactivity, and perceived learning outcomes. The results indicate that a majority of students perceive online learning applications as effective in facilitating flexible and accessible learning. However, some limitations were noted, particularly in terms of internet connectivity, user interface, and reduced face-to-face interaction. The study concludes that while online learning applications are generally well-received, their effectiveness can be improved through better technical support and instructional design. These findings provide valuable insights for educators and developers in optimizing digital learning environments.